1988
DOI: 10.1017/s0950268800029472
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of poliovirus-neutralizing antibodies 2–16 years after immunization with live attenuated vaccine. A seroepidemiologic survey in the mainland of Venice.

Abstract: A seroepidemiological survey was conducted on subjects who had received a full vaccination course with live attenuated poliovirus 2-16 years before. For strains 1 and 2 prevalence of seropositives and median values dropped gradually during the first 10 years; strain 3 showed a much earlier decline. Environmental displacement of wild poliovirus by the attenuated, less immunogenic strain might eventually induce a 'gap', should complacency hamper needed vaccination efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 7 publications
(6 reference statements)
2
3
0
Order By: Relevance
“…So, as expected, GMT values for poliovirus type 2 were always higher than those for poliovirus type 1 and both were higher than those for poliovirus type 3, when calculated by age group (Table 2). Studies conducted in the United States (1,8,13), Oman (17), Italy (2,6,12,(18)(19)(20), Finland (5), Israel (3), and South Africa (15) on antibody titers in OPV recipients monitored long-term concur with our results, demonstrating a decline in immunity and antibody geometric mean values. Overall, those surveys reported that the decline in immunity and GMT of neutralizing antibodies is related to intervals since the last OPV vaccination and not to gender, race, age at primary vaccination, or number of previous administrations.…”
Section: Discussionsupporting
confidence: 89%
“…So, as expected, GMT values for poliovirus type 2 were always higher than those for poliovirus type 1 and both were higher than those for poliovirus type 3, when calculated by age group (Table 2). Studies conducted in the United States (1,8,13), Oman (17), Italy (2,6,12,(18)(19)(20), Finland (5), Israel (3), and South Africa (15) on antibody titers in OPV recipients monitored long-term concur with our results, demonstrating a decline in immunity and antibody geometric mean values. Overall, those surveys reported that the decline in immunity and GMT of neutralizing antibodies is related to intervals since the last OPV vaccination and not to gender, race, age at primary vaccination, or number of previous administrations.…”
Section: Discussionsupporting
confidence: 89%
“…The highest antibody seroprevalence and GMTs in each age group were for P2 and the lowest was for P3. These results are similar to those of other countries, such as Brazil (21), Germany (22), the United States (23), Italy (24)(25)(26)(27), Belgium (28), Greece (29), Netherlands (30), and South Africa (31). Nates and colleagues in Argentina found that humoral immunity to P3 declined significantly over time (32).…”
Section: Discussionsupporting
confidence: 87%
“…Several of the OPV challenge studies (Table ) and serological surveys provide cross‐sectional data on the persistence of antibodies after vaccination, which show that antibody levels can drop below detectable levels in previously LPV‐infected or IPV‐vaccinated subjects ,. Other cross‐sectional serological data confirm the decrease both in the proportion of seropositive subjects and mean antibody titers as a function of time since the last vaccination …”
Section: Resultsmentioning
confidence: 87%